Strategi Bank Syariah dalam Penghimpunan Dana Pihak Ketiga (DPK) di Era Disrupsi Digital (Studi Kasus: PT. Bank Sumut KCP Syariah Panyabungan) - Salsabila Sandioriva; Septria Susanti (ARZUSIN, 2026)
Although digital transformation and the development of Islamic banking services have been widely studied, research specifically analyzing third-party fund (TPF) mobilization strategies at Islamic bank sub-branch offices in regional areas remains limited. This study aimed to analyze the strategies employed by PT Bank Sumut KCP Syariah Panyabungan to mobilize TPF in the era of digital disruption and identify the factors influencing the success of these strategies. The study employed a qualitative approach with a case study design. Informants were selected through purposive sampling and consisted of the head of the sub-branch office, customer service officers, customers, and community members associated with Islamic banking services. Data were collected through observation, semistructured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing and verification. The results showed that the TPF mobilization strategies were implemented through the optimization of fund mobilization products, improvement of service quality, direct promotion, utilization of mobile banking services, and strengthening of relationship marketing. The SWOT analysis results showed that the Strength–Opportunity (SO) strategy was the most appropriate alternative for increasing TPF mobilization by leveraging the bank’s internal strengths and external opportunities. This study emphasizes that successful TPF mobilization in the era of digital disruption requires the integration of digital transformation, service quality, relationship-based marketing, and Islamic financial literacy. The findings contribute to the development of studies on Islamic banking strategies and provide practical implications for Islamic banks in formulating more effective public fund mobilization strategies that are adaptive to developments in digital technology.